Analisis Pengaruh Kebijakan Deviden serta Leverage terhadap Keputusan Pendanaan - Joko, Fx Agus; Ka'aro, Hermeindito (Jurnal Widya Manajemen & Akuntansi, 2002)
This research examines and extents Kaaro' study (2001) that founded that there are significant relationships between leverage and dividend in high uncertainty conditions, but the association is disappear if business risk included in the model. This paper attempts to conduct Kaaro' study by including period analysis both in less uncertainty conditions and in high uncertainty conditions. Other attributes of pecking order theory also included in this study. This study supports Kaaro findings that there are significant associations between dividend and leverage in high uncertainty condition if business risk ignored. However, this study also finds that there are no strong relationship between dividend and leverage in less uncertainty condition even though the business risk variable is not included in the model. Other attributes that considered in this study partially support pecking order theory.